2004
DOI: 10.1111/j.1365-2516.2004.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between factor VIII:Ag and factor VIII in recombinant and plasma‐derived factor VIII concentrates

Abstract: A variety of plasma-derived (pd) and recombinant (r) factor VIII (FVIII) concentrates are used to prevent and treat bleeding in severe hemophilia A patients. A significant side effect of FVIII replacement is the development of FVIII neutralizing antibodies (inhibitors) in up to 30% of patients receiving FVIII concentrates. The FVIII protein content (FVIII:Ag) per unit of FVIII:C in FVIII concentrates, and how effectively the FVIII:Ag in FVIII concentrates binds to von Willebrand factor (VWF) may provide inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 32 publications
10
67
1
Order By: Relevance
“…This observation reflects previous findings in FVIII-deficient mice. 6 The VWF used in our studies is a plasma-derived preparation that contains trace amounts 9 Our results demonstrate that the in vitro pre-incubation of rFVIII with VWF reduced its immunogenicity to the level achieved with pdFVIII. These data suggest that the immunogenicity of rFVIII is not due exclusively to the reduced ability of rFVIII to bind to VWF, but that other mechanisms must be implicated.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 73%
“…This observation reflects previous findings in FVIII-deficient mice. 6 The VWF used in our studies is a plasma-derived preparation that contains trace amounts 9 Our results demonstrate that the in vitro pre-incubation of rFVIII with VWF reduced its immunogenicity to the level achieved with pdFVIII. These data suggest that the immunogenicity of rFVIII is not due exclusively to the reduced ability of rFVIII to bind to VWF, but that other mechanisms must be implicated.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 73%
“…macropinocytosis, 75 but is also in agreement with findings that a significant portion of FVIII:Ag present in rFVIII preparations is not able to associate with VWF. 54,[65][66][67][68] Delignat and co-workers reassessed these findings in a model of FVIII-deficient mice. The animals were treated by intravenous injection with rFVIII, which was either pre-incubated or not with a 50-fold molar excess of purified VWF.…”
Section: 70mentioning
confidence: 94%
“…It was suggested that this portion of rFVIII:Ag may trigger the specific immune response in patients. 54,[65][66][67][68] The exposed VWF-binding site on FVIII, incidentally, may be occupied by anionic phospholipids which were suggested to have additional implications for the immune response. …”
mentioning
confidence: 99%
“…More extensive pre-processing of plasma-derived FVIII possibly caused its lower signals as compared with those of the full size recombinant FVIII. Other characteristics include heterogeneity of full size FVIII due to the natural variability in the B-domain length and other properties, previously compared between various FVIII products (42)(43)(44)(45). A residual binding of both recombinant FVIII variants to the CR doublets non-active for plasma-derived FVIII was attributed to a nonspecific component.…”
Section: Expression Of Ldlr Fragments-mentioning
confidence: 98%